Harnessing microbes and plants for bioremediation of heavy metal contaminants: Current paradigms and future perspectives - Anjuman Ayub; Atif Khurshid Wani; Suhaib Mohd Malik; Mehvish Ayub; Chirag Chopra; Reena Singh; Tabarak Malik (Environmental Challenges, 2025)
The increasing contamination of the environment by heavy metals from industrial, agricultural, and urban activities cause significant risks to the ecosystems and human health. Heavy metals are toxic to aquatic life, plants, and microorganisms, worsening environmental degradation. However, various species have evolved natural detoxification mechanisms, making bioremediation an attractive strategy for environmental preservation. Bioremediation harnessing the natural detoxification capabilities of microorganisms and plants, has emerged as a sustainable and environment friendly alternative to traditional remediation methods. Microorganisms, particularly bacteria employ metabolic pathways to transform or sequester toxic metals, reducing their bioavailability, while certain plants uptake and accumulate heavy metals in their tissues for phytoremediation. The combined use of microbial consortia and plant systems enhances metal detoxification, stabilization, and uptake, offering improved efficiency across various environmental conditions. This study provides a comprehensive account of the recent advancements in the use of microorganisms and plants as sustainable strategies to detoxify heavy metal contaminants. It discusses the potential mechanisms employed by the microbes and plants to mineralize these emerging pollutants in the environment. Further we weigh the pros and cons of the plant and microbe-based remediation strategies, emphasizing their potential integration with conventional methods to develop comprehensive, sustainable solutions for heavy metal pollution control.